RELATIONAL DYNAMICS OF ACCESSIBLE TOURISM IN FRANCE, SPAIN AND MOROCCO - Jose Maria Prat-Forga; Gemma Cànoves-Valiente (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2012)
The knowledge on the tourist actors of the territory and their relations is a basic element for the active management of any tourist destination, since they have a special importance for the strategies and the actions that must be undertaken to adapt to the new conditions of the context. These conditions are characterized, among other things, by the disintermediation and the new habits of the tourist demand, in which the experience, the major activity in the destination and the discovery and self-organization are key factors. After reviewing the main features of accessible tourism and its situation in the current world context, this paper will examine the correlation in three specific Mediterranean countries (France, Spain and Morocco) between the level of development of accessible tourism and the relational dynamics generated by the actors involved in it. For this particular purpose, the Analysis of Social Networks and the Analysis of Contents of Social Networks will be applied.